Using Content Analysis (CA) in Seeking the Opportunities for Alumni of English Department in Newspapers - Budianto Hamuddin (ELT-Lectura, 2016)
This present study is designed to analyze a discourse of recent job vacancies in media. It aims tohelp and gives a perspective regarding of the opportunity offered by media on their job vacancy pages. The data of this study based its collection of 4.973 job vacancy ads in 2 largest newspapers in Riau Province from March to April 2015. Using Content analysis in discourse analysis area as the framework this study tries to answer a question in alumni’s mind “Where do we go after graduate?”. The analysis of this study reveals that the alumni must see the opportunities offered both in non-teaching and the teaching category after they graduated from university. This study shows that teaching category offers 149 (3%) positions and non-teaching category offers more opportunities 1.668 (44%) positions from the total collections of 4.973 JV ads. The data also found the 10 most frequently jobs and the requirements posted in newspaper either in teaching or non-teaching category.